Coastal engineering : processes, theory and design practice - Reeve, Dominic; Chadwick, Andrew, 1960-; Fleming, Christopher (New York : Spon Press, 2012)
'Historically, much harm has been done by well-meaning coastal engineering attempts, which seemed like good ideas on paper but which failed to allow for practical issues. For this reason, it is vital that theories and models are well grounded in practice. This second edition brings the models and examples of practice up to date. It has expanded coverage of tsunamis and generating energy from waves to focus both on the great dangers and the great opportunities which the ocean presents to the coastal zone. With an emphasis on practice and detailed modelling, this is a thorough introduction to all aspects of coastal processes, morphology and design of coastal defences. It describes numerous case studies to illustrate the successful application of mathematical modelling to real world practice. A must-have book for engineering students looking to specialize in coastal engineering and management'--
Keywords: Coastal engineering; TECHNOLOGY & ENGINEERING / Civil / General; TECHNOLOGY & ENGINEERING / Civil / Dams & Reservoirs; TECHNOLOGY & ENGINEERING / Environmental / General